The effects and cost‐effectiveness of an empowerment‐based self‐care programme in patients with chronic heart failure: A study protocol. (27th August 2019) - Yu, Doris S. F.; Li, Polly W. C.; Yue, Sunny C. S.; Wong, John; Yan, Bryan; Tsang, Kin Keung; Choi, Kai Chow
Abstract: Aim: This study aims to evaluate the effects of a 12‐week empowerment‐based self‐care programme on the cognitive, psychological and behavioural aspects of self‐care, health‐related quality of life and unplanned hospital service use of chronic heart failure patients and to estimate its cost‐effectiveness in reducing unplanned service use. Study design: Randomized controlled trial with cost‐effectiveness analysis. Methods: The study will recruit 236 community‐dwelling Chinese patients with chronic heart failure from regional hospitals in Hong Kong. Patients will be randomized in blocks to attend either the 12‐week empowerment‐based self‐care programme or a didactic education programme. Central to the empowerment‐based model is that the patients are the primary decision makers in self‐care and act autonomously to manage the disease. Collaborative approach and interactive teaching strategies are used to optimize patients' engagement and knowledge translation to real‐life practice. Outcome evaluation on self‐care maintenance and management, symptom perception, self‐care confidence, self‐care knowledge, health‐related quality of life and health service use will take place at baseline, on completion of the programme and at 12 weeks thereafter. Generalized estimating equations and Cox regression examine the intervention effects. Bootstrapping technique will be conducted to examine the cost‐effectiveness of the intervention. The study is formally funded in December 2016. Discussion: Chronic heart failure is associated with high level of hospital admissions, of which 40% is avoidable through effective self‐care. Although self‐care confidence is known to improve self‐care, no structured educative method has been developed to enhance this attribute. This study addresses this research gap with a stringent application of theory and research design. Impact: The study illustrates the application of the empowerment model for self‐care enhancement in patients with chronic heart failure. The findings will inform the ways and values of this care model to enhance the disease management of this expanding clinical cohort. Abstract : 目的: 本研究旨在评估一个12周的基于赋权的自我护理项目对于认知、心理和行为方面的自我护理, 健康相关生活质量和慢性心力衰竭病人的计划外医院运送服务和估算其成本效益减少计划外的运送服务使用。 研究设计: 成本效益分析的随机对照实验。 方法: 本研究将从香港地区医院招募236名居住在社区的中国慢性心力衰竭患者。患者将被随机分组, 参加为期12周的基于授权自我护理项目或说教教育项目。以授权为基础的模式的核心是, 患者是自我护理的主要决策者, 并自主采取行动来管理疾病。采用协作方法和交互式教学策略以优化患者的参与和将知识转化为现实生活中的实践。将在基线、项目完成时和在12周后对自我护理维护和管理、症状感知、自我护理信心、自我护理知识、健康相关生活质量和健康服务使用的结果进行评估。广义评估方程和Cox回归分析用于检验干预效果。引导技术将用于检查干预的成本效益。该研究于2016年12月正式获得资金赞助。 讨论: 慢性心力衰竭直接相关于高住院率, 其中40%的住院率可通过有效的自我护理避免。尽管自我护理信心可以改善自我照顾, 但是还没有一种结构化的教育方法可以增强这种自信。本研究通过严格的理论应用和研究设计来弥补这一研究空白。 影响: 本研究阐释了授权模式在增强慢性心力衰竭患者自我照顾中的应用。本研究结果将为该护理模式的方法和价值提供信息, 以提高逐渐扩大的临床治疗患者队伍的疾病管理。